Performance analysis of wireless sensor network with load balancing for data transmission using xbee zb module - Ahmad Yusuf Ardiansyah; Riyanarto Sarno (Institute of Advanced Engineering and Science, 2020)
In general, research in the field of wireless sensor network (WSN) has never discussed the reliability aspect of network routing with router devices that can find new routes when damage occurs. To date, overloaded routers will be ignored without any response that gives control which can reduce the quality of network performance. Therefore, we propose research using the AODV routing, and Mesh routing algorithm to find other routes as an alternative when problems occur and using the Round Robbin based xbee algorithm on providing load balance control carried out by the router. The experiments on the performance of non-balancing networks and balancing were conducted. Both trials used quality of service (QoS) parameters as a guarantee of performance to be more effective and in line with expectations. Measurements performed by testing the parameters of packet loss, delay, throughput, and fault tolerance. The network performance in finding other alternative routes has been successfully carried out by transmitting 100 packets from the end device node to the coordinator node via the router based on distance variations from 0 to 100 meters. The recovery time required by the dead router to find another route was 10 seconds, this was related to the parameter delay, and fault tolerance. The experimental results of the non-balancing system showed an average 20 % packet loss in one transmission, meanwhile the packet loss was smaller than the previous experiment by 37%. Therefore, the WSN with balancing system was proven to be more effective that could improve QoS performance by 17%.